Peningkatan Pemahaman Siswa Tentang Swamedikasi Diare Melalui Edukasi Interaktif - Fadhli, Haiyul; Wulandari, Venny; Sandra Tsalsabila Ananto, Deswita; Putri Pratiwi, Amanda; Arif Arsaf, Mohammad (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: The practice of self-medication for diarrhea remains irrationally performed by the community, including students. The lack of health education in schools contributes to students' lack of knowledge about self-medication of diarrhea. The purpose of this activity is to improve students' understanding of diarrhea self-medication through an interactive educational approach. Methods: This community service utilized a descriptive observational method, incorporating a pretest and posttest approach. Interventions were conducted through interactive discussions and question-and-answer sessions. They are encouraging active student participation. Results: Before the intervention, only three students could correctly answer questions regarding self-medication for diarrhea. After interactive education, the level of understanding increased significantly to 80%. Conclusion: Interactive education has proven effective in enhancing students' knowledge of self-medication for diarrhea. This approach holds potential for sustainable implementation in school health education programs, aiming to raise students' awareness and understanding.